Effect of turbo cyclone vane angles on performance and emissions of a 1000 cc engine - Monasari, Ratna; Qosim, Nanang; Jaya, Kukuh Laksana; Pratama, Argiansyah Bayu (Politeknik Negeri Lhokseumawe, 2025)
The installation of a turbo cyclone in the intake manifold aims to increase airflow turbulence, thereby improving the air–fuel mixture process inside the combustion chamber. This study investigates the effects of turbo cyclone implementation on the performance, fuel consumption, and exhaust emissions of a 1000 cc engine. The cyclone was designed with six fixed vanes at angles of 30°, 45°, and 60°, and tested using two fuels: RON 90 and RON 92. Engine performance was measured with a dynamometer across 1000–6000 rpm, fuel consumption was evaluated using Specific Fuel Consumption (SFC), and exhaust emissions were analyzed with a gas analyzer. Results indicate that the 60° vane angle delivers the best overall performance, achieving a maximum power of 34.1 HP, peak torque of 57.4 Nm, and the lowest SFC of 93.33 g/kWh. Additionally, CO and HC emissions were reduced by up to 40% compared to the baseline (non-cyclone) condition. Among the tested fuels, RON 92 consistently provided better performance and lower emissions, highlighting its higher combustion efficiency. These findings demonstrate that the turbo cyclone (particularly at a 60° vane angle) effectively improves engine efficiency, enhances output, and reduces harmful emissions.